Prenatal detection of novel compound heterozygous variants of the PLD1 gene in a fetus with congenital heart disease - Zhu, Linyan; Chen, Mei; Shi, Yubo; Huang, Xiaxi; Ding, Huiqing (Frontiers in Genetics, 2024)
BackgroundCongenital heart disease (CHD) is the most common birth defect and heart valve defects are the most common cardiac defect, accounting for over 25% of all congenital heart diseases. To date, more than 400 genes have been linked to CHD, the genetic analysis of CHD cases is crucial for both clinical management and etiological determination. Patients with autosomal-recessive variants of PLD1 are predisposed to Cardiac Valvular Dysplasia-1 (CVDP1), which predominantly affects the right-sided heart valves, including the pulmonic, tricuspid, and mitral valves.MethodsDatabases were utilized to predict the impact of the c.1062-59A>G variant on splicing. Whole-exome sequencing (WES), reverse transcription polymerase chain reaction (RT-PCR), Sanger sequencing, and TA clone sequencing were conducted on both the parents and the fetus.ResultsA compound heterozygous variation in the PLD1(NM_002662.5):c.1937G>C (p. G646A) from the father and PLD1(NM_002662.5):c.1062-59A>G from the mother, was identified and confirmed in the fetus. The c.1937G>C (p. G646A) and the c.1062-59A>G variants were all classified as variant of uncertain significance (VUS) per ACMG guidelines. RT-PCR and TA clone sequencing revealed a 76-bp intronic insertion and exon 11 skipping in the proband and her mother’s transcripts, causing a frameshift and premature stop codon in PLD1. Consequently, after being informed about the risks of their variant of unknown significance (VUS), the couple chose pre-implantation genetic testing for monogenic disorders (PGT-M) and had a healthy child.ConclusionOur study identified novel variants to expand the mutation spectrum of CHD and provided reliable evidence for the recurrent risk and reproductive care options.